2023
DOI: 10.1186/s12944-023-01795-2
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related differences in the hypertriglyceridemic-waist phenotype in association with hyperuricemia: a longitudinal cohort study

Abstract: Background There is limited longitudinal evidence supporting the association between the hypertriglyceridemic-waist (HTGW) phenotype and hyperuricemia. This study aimed to examine the longitudinal relationship between hyperuricemia and the HTGW phenotype among males and females. Methods A total of 5562 hyperuricemia-free participants aged 45 or over from the China Health and Retirement Longitudinal Study (mean age: 59.0) were followed for 4 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…This study extends the use of lipid ratios and fills the gaps in previous research, suggesting that the NHHR might be a promising marker for predicting HUA. Notably, cohort research has confirmed a close relationship between dyslipidaemia and the incidence of HUA [ 32 34 ]. Hence, from the perspective of lipid management, the prevention and treatment of HUA could offer important clinical benefits.…”
Section: Discussionmentioning
confidence: 99%
“…This study extends the use of lipid ratios and fills the gaps in previous research, suggesting that the NHHR might be a promising marker for predicting HUA. Notably, cohort research has confirmed a close relationship between dyslipidaemia and the incidence of HUA [ 32 34 ]. Hence, from the perspective of lipid management, the prevention and treatment of HUA could offer important clinical benefits.…”
Section: Discussionmentioning
confidence: 99%
“…17 In a 4-year follow-up of 5562 people aged 45 years or older without hyperuricemia, the HTGW phenotype was reportedly associated with a risk of hyperuricemia, especially in women. 18 Moreover, in a rural population in China, individuals with HTGW were 4.54 times more likely to develop hyperuricemia than those with normal TG normal waist (NTNW) levels. 19 Another study targeting patients with rheumatoid arthritis revealed a close relationship between hyperuricemia and the HTGW phenotype.…”
Section: Introductionmentioning
confidence: 99%